Determinants of Firms' Exit in the Indian Electronic Industry - Singh, Rajeev; Irfan, Mohd (Prabandhan: Indian Journal of Management, 2010)
The beginnings of the Indian electronics industry reach back to the early 1960s. At that time, the electronics industry concentrated on developing and maintaining fundamental communication systems, such as radio-broadcasting, telephonic and telegraphic communication, and aimed at enhancing defense capabilities. Later, at the end of the 1980s, the electronics industry experienced a rapid growth as a result of outstanding economic changes. The latter were due to the liberalization and globalization efforts of the Indian government in order to trigger off economic growth and to promote the creation of an export-oriented electronics industry. By 1991, foreign and domestic private investments were encouraged. Foreign investment norms were eased, 100 % foreign equity was allowed, custom tariffs were reduced and many consumer electronic products were delicensed. These initiatives attracted a large amount of foreign investment and collaborations.